KEDUDUKAN HUKUM PEMEGANG HAK MILIK ADAT YANGDI BERIKAN HAK GUNA BANGUNAN DI ATAS TANAH NEGARA (STUDI DI DESA SUNGAI BURUNG KECAMATAN SEGEDONG KABUPATENMEMPAWAH) - NIM. A1012171086, LEONARDO SAMOSIR (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstracThe research was conducted against the background of the Confiscation of Beny Tjockrosaputro's assets in the case of using ASABRI Funds in 2021, which was sentenced to a criminal sentence, resulting in the confiscation of assets, one ofwhich was land in Sungai Burung village, Segedong district, Mempawah district. Adat which began in 1992, because this research is aimed at seeking legal certainty for communities who have customary land owned by customary owners related to the confiscation of assets by the state, so this research is given the theme